Criminology: a sociological introduction - Carrabine, Eamonn (Routledge, 2014)
"Building on the success of the second edition, Criminology: A Sociological Introduction offers a comprehensive overview of the study of criminology, from early theoretical perspectives to pressing contemporary issues such as the globalization of crime, crimes against the environment and state crime. Authored by an internationally renowned and experienced group of authors in the Sociology department at Essex University, this is a truly international criminology text that delves into areas that other texts may only reference.This new edition will have increased coverage of psychosocial theory, as well as more consideration of the social, political and economic contexts of crime in the post-financial-crisis world. Focusing on emerging areas in global criminology, such as green crime, state crime and cyber crime, this book is essential reading for criminology students looking to expand their understanding of crime and the world in which they live"--